A Cascaded Synchronous Buck Converter for Light Electric Vehicle Charging Applications - Mohammad Faisal Akhtar; Siti Rohani Sheikh Raihan; Nasrudin Abdul Rahim; Mohd Khairil Rahmat (International Journal of Integrated Engineering, 2024)
In this work, a cascaded synchronous DC-DC converter topology is presented which is suitable for high current applications. In this topology, a synchronous buck converter is cascaded with a series capacitor synchronous buck converter, which exhibits very low step-down voltage gain – thus translating to a high current gain.. For this work, this converter is applied for charging a 24 V, 10 A h Lithium-ion (Li-ion) battery. The constant-current constant-voltage (CC/CV) technique is employed with the proposed converter for this application. Simulations for the system were carried out on MATLAB Simulink, using the SimPowerSystems toolbox. The converter operation is observed to align with a typical CC/CV charging profile, with a 93.3% charging efficiency. Consequently, this topology may be integrated into an off-board charger for light electric vehicles (LEVs) such as e-bikes and three-wheeler e-rickshaws – which are typically used in public transportation. Suitability of the given converter is further corroborated by the observed charging efficiency. This work can potentially aim to address the issue of downtime that drivers of electric three-wheelers may face during peak operating hours. Consequently, this can open doors for further adoption of light electric vehicles for public transportation.